2015
DOI: 10.1016/j.nicl.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-cerebellar connectivity is increased in primary lateral sclerosis

Abstract: Increased functional connectivity in resting state networks was found in several studies of patients with motor neuron disorders, although diffusion tensor imaging studies consistently show loss of white matter integrity. To understand the relationship between structural connectivity and functional connectivity, we examined the structural connections between regions with altered functional connectivity in patients with primary lateral sclerosis (PLS), a long-lived motor neuron disease. Connectivity matrices we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…Indeed, dysfunctions in the sensorimotor network (including the bilateral precentral gyrus, posterior gyrus, and paracentral lobule) have been well validated by previous ALS studies, and these are associated with impaired corticospinal fiber integrity . Additionally, in agreement with our finding of RK reduction in the cerebellar lobe, structural atrophy and dysfunction in the cerebellum have been detected in ALS and are related to poor motor functioning . Furthermore, microstructural impairment in the middle corpus callosum is another consistent feature of ALS, as previous DTI studies have reported .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, dysfunctions in the sensorimotor network (including the bilateral precentral gyrus, posterior gyrus, and paracentral lobule) have been well validated by previous ALS studies, and these are associated with impaired corticospinal fiber integrity . Additionally, in agreement with our finding of RK reduction in the cerebellar lobe, structural atrophy and dysfunction in the cerebellum have been detected in ALS and are related to poor motor functioning . Furthermore, microstructural impairment in the middle corpus callosum is another consistent feature of ALS, as previous DTI studies have reported .…”
Section: Discussionsupporting
confidence: 91%
“…AD pathology could not only lead to synaptic alterations [Baloyannis et al, 2000] in some cerebellar regions and cerebral regions (mostly in the frontal areas) [Braak and Braak, 1991] in MCI subjects, but also alter the indirect (via the relay of the thalamus and/or pons) long-range pathway between the cerebral and cerebellar regions, thus resulting in abnormal cognitive function (see the review in Egidio and Stefano [2012] for more details). However, few previous studies have shown such a long-range cerebrocerebellar functional connectivity abnormality in the early stage of AD, especially for the subjects without observable structural difference [Hanyu et al, 1993;Meoded et al, 2015]. Our result suggests that, by using dFC, we can detect subtle changes in the large-scale cerebrocerebellar functional integration for MCI subjects.…”
Section: Most Discriminative Connectionsmentioning
confidence: 54%
“…40 The other study, which searched for new patterns of function connectivity, found increased functional connectivity between the cerebellum and several cortical regions that were not structurally connected. 41 It is not clear if the increased functional connectivity reflects loss of selective activation or develops as a form of compensation for the loss of motor cortical circuits.…”
Section: Pathophysiologymentioning
confidence: 99%